ANALISA NILAI KALOR BAHAN BAKAR BOILLER FIBER DAN CANGKANG - Nopita, Dian; Nuramal, Agus; Supardi, Nurul Iman (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
Fiber and shell are widely use solid fuels in steam boilers. These fuels are waste products generated from palm oil processing. The purpose of this study is to analyze the heating value of fiber and shell. This study used 12 fuel samples, consisting of 3 pure fiber samples, 3 pure shell samples, 3 mixed samples with a composition of 90% fiber and 10% shell, and 3 mixed samples with a composition of 80% fiber and 20% shell, to analyze the calorific value. The weight of each sample is 1 gram. Calorific value is used to determine the high calorific value. The use of different samples produces different heating values, resulting in different high heating values. These different high heating values are then used to determine the low heating value, resulting in different low heating values. In this study, each boiler fuel has a different Low Heating Value (LHV). The highest low heating value is owned by pure fiber fuel with a value of NA (Not Available). While the smallest low heating value of boiler fuel is owned by a mixed type consisting of 90% fiber and 10% shell with a value of 179358,51 Kj/Kg.